Molecular mechanism of hyperactive tooth root formation in oculo-facio-cardio-dental syndrome - Min Soe, Kyaw; Ogawa, Takuya; Moriyama, Keiji (Frontiers in Physiology, 2022)
Mutations in the B-cell lymphoma 6 (BCL6) interacting corepressor (BCOR) cause oculo-facio-cardio-dental (OFCD) syndrome, a rare X-linked dominant condition that includes dental radiculomegaly among other characteristics. BCOR regulates downstream genes via BCL6 as a transcriptional corepressor. However, the molecular mechanism underlying the occurrence of radiculomegaly is still unknown. Thus, this study was aimed at identifying BCOR-regulated genetic pathways in radiculomegaly. The microarray profile of affected tissues revealed that the gene-specific transcriptional factors group, wherein nucleus factor 1B, distal-less homeobox 5, and zinc finger protein multitype 2 (ZFPM2) were the most upregulated, was significantly expressed in periodontal ligament (PDL) cells of the diseased patient with a frameshift mutation (c.3668delC) in BCOR. Wild-type BCOR overexpression in human periodontal ligament fibroblasts cells significantly hampered cellular proliferation and ZFPM2 mRNA downregulation. Promoter binding assays showed that wild-type BCOR was recruited in the BCL6 binding of the ZFPM2 promoter region after immunoprecipitation, while mutant BCOR, which was the same genotype as of our patient, failed to recruit these promoter regions. Knockdown of ZFPM2 expression in mutant PDL cells significantly reduced cellular proliferation as well as mRNA expression of alkaline phosphatase, an important marker of odontoblasts and cementoblasts. Collectively, our findings suggest that BCOR mutation-induced ZFPM2 regulation via BCL6 possibly contributes to hyperactive root formation in OFCD syndrome. Clinical data from patients with rare genetic diseases may aid in furthering the understanding of the mechanism controlling the final root length.